2020
DOI: 10.3390/life10090170
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdovirus Infection Is Dependent on Serine/Threonine Kinase AP2-Associated Kinase 1

Abstract: Rabies virus (RABV) causes a fatal neurological disease in both humans and animals. Understanding the mechanism of RABV infection is vital for prevention and therapy of virulent rabies infection. Our previous proteomics analysis based on isobaric tags for relative and absolute quantitation to identify factors revealed that RABV infection enhanced AP-2-associated protein kinase 1 (AAK1) in N2a cells. In this study, to further confirm the role of AAK1, we showed that RABV infection increased the transcription an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In addition to viral receptors, increasing evidence indicates that the entry of many viruses involves engagement with distinct plasma membrane components as entry factors, each of which is important ( 8 ). Recent studies have reported that integrin β1 ( 14 ) and AP-2-associated protein kinase 1 ( 15 , 16 ) play roles in RABV entry; however, the key host factors involved in the endocytosis of RABV remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to viral receptors, increasing evidence indicates that the entry of many viruses involves engagement with distinct plasma membrane components as entry factors, each of which is important ( 8 ). Recent studies have reported that integrin β1 ( 14 ) and AP-2-associated protein kinase 1 ( 15 , 16 ) play roles in RABV entry; however, the key host factors involved in the endocytosis of RABV remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…When stably expressed, BMP2K negatively regulates osteoblast differentiation and mineral deposition. Thus, BMP2K, including a nuclear localization signal and a glutamine-rich region, is demonstrated to be implicated in the regulation of the cell differentiation process [44].…”
Section: Modulation Of Notch Pathwaymentioning
confidence: 99%
“…AAK1 is shown to be required for the infection of Rabies virus (RABV). AAK1 knockdown decreases, and AAK1 knockout inhibits, RABV infection in N2a cells [44]. Wang et al reported that phosphorylation of AP2 by AAK1 was responsible for RABV entry.…”
Section: Numb-associated Kinases As Potential Broadspectrum Antiviral...mentioning
confidence: 99%
“…The rescued virus was confirmed in NA cells by a direct fluorescent antibody assay (dFA) with FITC-labelled anti-RABV N antibodies, as described previously [ 15 ]. The IL-25 and RABV M expression was confirmed by western blotting as described previously [ 16 ] using mouse anti-IL-25 and anti-RABV M antibodies. Protein fingerprints were shown using Fine-do 96 (Tanon, China).…”
Section: Construction Of Recombinant Full-length Cdna Clones and Resc...mentioning
confidence: 99%
“…Peripheral blood was collected on days 14 and 21 after immunization, and serum was used to determine VNA levels using fluorescent antibody virus neutralization (FAVN) tests as described previously [ 18 ]. The IgG1 and IgG2a in serum were determined with anti-IgG1 and anti-IgG2a antibodies using western blot as described previously [ 16 ]. Levels of IgG2c in serum were determined using Enzyme-Linked Immunosorbent Assay (ELISA) Kits (Meimian Biotechnology, Jiangsu, China) according to the manufacturer’s instructions.…”
Section: Pathogenicity Of Rabv In Adult Micementioning
confidence: 99%